Pengembangan Instrumen Asesmen Kompetensi Minimum (AKM) Numerasi Model Pisa Dengan Konteks Musi Rawas Kelas V Sekolah Dasar - Trie Utari; Agus Susanta; Irwan Koto (UNIB Press, 2024)
This study aims to analyze the logical feasibility, empirical and numeracy ability profile of students. Product development of the Minimum Competency Assessment (MCA) numerical instrument PISA model with the context of Musi Rawas for 5th grade Elementary School. This research is a Research and Development (R&D) study and used the ADDIE model. The subjects of the research was the 5th grade students of SDN 1 Terawas, totaling 20 students to test eligibility empirically, and the 5th grade students of SDN Pasenan, totaling 18 students to analyze the profile of numeracy abilities. The numerical MCA consists of 17 questions in the form of multiple choice, complex multiple choice, and matching which are arranged using the MCA numeracy cognitive level and PISA 1-3 levels. Data data logically validity results has an index of more than 0.4 and is declared valid and logical. The results of empirical validity are 16 valid questions and 1 invalid question. The reliability value is 0.89 as